IMPLEMENTASI PENDIDIKAN AKHLAK MULIA DI PONDOK PESANTREN SAWABIQUL HIMAM NGROTO CEPU BLORA - Imam Fatoni (Pascasarjana IAIN Sorong, 2021)
Abstract This study aims to describe and analyze the implementation of noble character education and its supporting and inhibiting factors. The research approach is qualitative which is carried out at Sawabiqul Himam Ngroto Islamic Boarding School with the research subjects being Islamic boarding school caregivers and religious teachers. For data collection, interviews, observations, documentation and focus group discussions were conducted. The data analysis techniques of this research are data reduction, data display and data verification and then draw conclusions from the data that has been presented in stages to become research findings. This paper concludes that the caretakers of the Islamic boarding school and the ustad have tried to implement noble character education to the students, both from the aspect of exemplary education, habituation, attention, giving advice, and educating punishment. Supporting factors are the caregivers of the Islamic boarding school who seek to socialize the vision and mission of the Islamic boarding school to the residents of the boarding school and the cooperation between the ustad and other components. The inhibiting factor is the inadequate prayer room and the allocation of funds for Islamic boarding school activities. Keywords: Implementation, Education, Noble Morals